1990
DOI: 10.1136/hrt.63.3.157
|View full text |Cite
|
Sign up to set email alerts
|

What is meant by a "controlled" ventricular rate in atrial fibrillation?

Abstract: Reduction of a rapid ventricular rate in atrial fibrillation results in a longer diastolic filling period and a higher left ventricular stroke volume but this is offset by reduced contractility and fewer beats per minute; the net effect on cardiac output is uncertain. Sequences of stroke distances were measured by Doppler ultrasound in 60 resting patients with atrial fibrillation to determine the relation between ventricular rate and linear cardiac output. The slope of the cardiac output/ventricular rate relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
5

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(73 citation statements)
references
References 11 publications
1
67
0
5
Order By: Relevance
“…In order to prevent the development of congestive heart failure, it is important to control the heart rate during AF to ≤130 bpm. 114 In the RACE II (Rate Control Efficacy in Permanent Atrial Fibrillation: a Comparison between Lenient versus Strict Rate Control II) study, the incidence rates of symptoms and adverse events and the severity of heart failure did not differ between patients receiving lenient rate control with a target resting heart rate of <110 bpm and those receiving strict rate control with a target resting heart rate of <80 bpm and a target heart rate of <110 bpm during moderate exercise. 115 However, this finding does not mean that a target resting heart rate of 100~109 bpm is sufficient.…”
Section: Indications For and Methods Of Heart Rate Controlmentioning
confidence: 99%
“…In order to prevent the development of congestive heart failure, it is important to control the heart rate during AF to ≤130 bpm. 114 In the RACE II (Rate Control Efficacy in Permanent Atrial Fibrillation: a Comparison between Lenient versus Strict Rate Control II) study, the incidence rates of symptoms and adverse events and the severity of heart failure did not differ between patients receiving lenient rate control with a target resting heart rate of <110 bpm and those receiving strict rate control with a target resting heart rate of <80 bpm and a target heart rate of <110 bpm during moderate exercise. 115 However, this finding does not mean that a target resting heart rate of 100~109 bpm is sufficient.…”
Section: Indications For and Methods Of Heart Rate Controlmentioning
confidence: 99%
“…İstira-hat halindeki atrial fibrilasyonlu bir kalbin optimal vuru sayısı normalden yüksek olabilir. Hemodinamik açıdan ideal atım sayısı ortalama dakikada 90 dolaylarındadır (3). Atrial fibrilasyonda ventrikül hı-zını kontrol etmek amacıyla digoksin önceden beri kullanılmaktadır.…”
Section: Discussionunclassified
“…Anti-arrhythmic drugs in the classes Ia, Ic and III have this property. Digoxin, however, which is widely used in established fibrillation to slow atrioventricular conduction, actually shortens atrial refractory period and is ineffective in preventing atrial fibrillation developing and actually prolongs the duration of bouts of atrial fibrillation (Rawles et al, 1990).…”
Section: Methods Of Cardioversionmentioning
confidence: 99%
“…More usually the ventricular rate is fast and this is associated with short diastolic filling periods and low cardiac output. Rawles (1990) recently showed that the optimum ventricular rate at rest in atrial fibrillation was about 90 beats min-' rather than 70 beats min-' which is the optimum in sinus rhythm. He hypothesised that the higher rate was required in atrial fibrillation to compensate for the loss of effective atrial contraction.…”
Section: Aims Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation